2021
DOI: 10.1111/ctr.14329
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in heart transplant recipients—A seroprevalence survey

Abstract: The clinical spectrum of COVID‐19 in heart transplant recipients has not been fully defined, because asymptomatic and sub‐clinical cases are difficult to capture. Seroprevalence surveys are an important tool to identify not just cases that have come to clinical attention, but all previously infected recipients. We performed a seroprevalence survey of the adult heart transplant program at a large New York City Hospital System. A total of 232 (87% of recipients being followed) subjects were tested, of whom 37 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…There is an extensive literature in the context of clinical profile and outcome of COVID-19 in SOT [14] including kidney [15][16][17], liver [18], lung [19], and heart [20,21]. Transplantation activity ceased around the world during the COVID-19 peak, but it is estimated that postponing transplantation will result in excess of deaths [22] and hence depending on the COVID-19 surge and available resources, the transplantation should be resumed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an extensive literature in the context of clinical profile and outcome of COVID-19 in SOT [14] including kidney [15][16][17], liver [18], lung [19], and heart [20,21]. Transplantation activity ceased around the world during the COVID-19 peak, but it is estimated that postponing transplantation will result in excess of deaths [22] and hence depending on the COVID-19 surge and available resources, the transplantation should be resumed.…”
Section: Discussionmentioning
confidence: 99%
“…Mild cases (73% vs 43%; p-value = 0.1) were higher and there were fewer cases (20% vs 9%; p-value = 0.69) with severe COVID-19 in post-COVID-19 mucormycosis. Among the laboratory profile, lymphopenia [12 (10-18) vs 20 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26); p-value = 0.15] and higher neutrophil-lymphocyte ratio [7 (4.6-8.3) vs 3.85 (3.3 -5.8); p-value = 0.5] was more associated with post-COVID-19 mucormycosis.…”
Section: Comparison Of Covid-19 Course Of the Historical Cohort Who Had Not Developed Post-covid-19 Mucormycosismentioning
confidence: 99%
“…Solid-organ transplant recipients are among the groups for whom vaccination is a priority. The seroprevalence of COVID-19 was found to be comparable in HT patients and in the general population, suggesting comparable susceptibility ( 7 ). In heart transplant (HT) recipients, vaccination against COVID-19 is associated with a lower risk of infection [hazard ratio (RR), 0.41; 95% CI, 0.30–0.56], hospitalization (RR, 0.29; 95% CI, 0.14–0.61) and death (RR, 0.19; 95% CI, 0.05–0.82), with no transplantation-specific adverse events ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 95%
“…COVID-19 is a major concern in solid-organ transplant (SOT) recipients, which have a mortality rate of up to 20% [ 1 , 2 ], and a 30% increased risk of death or use of mechanical ventilation [ 3 ]. In particular, heart transplant recipients have a more severe clinical course compared with the general population [ 4 ] and an estimated fatality rate of 25% [ 5 ]. Although they seem to not be at a higher risk of transmission [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, heart transplant recipients have a more severe clinical course compared with the general population [ 4 ] and an estimated fatality rate of 25% [ 5 ]. Although they seem to not be at a higher risk of transmission [ 4 ]. Some studies demonstrated that SOT recipients hospitalized with COVID-19 showed similar overall outcomes as hospitalized non-SOT recipients with other chronic conditions (obesity, diabetes, and hypertension), suggesting that chronic immunosuppression may not be an independent risk factor for poor outcomes in COVID-19 patients requiring hospitalization [ 6 ].…”
Section: Introductionmentioning
confidence: 99%